Análise pluviométrica do estado de São Paulo 1994-2014 - Antunes, Vitor Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper addresses the analysis of previous studies about the precipitation int São Paulo state, but most of all the PhD thesis of the professor Sant'Anna Neto, which focus on the behavior of the precipitations in Sao Paulo state. The Present study focus on updating the data used by the professor for the period of 1994 - 2014, and by creating precipitation graphs and maps, an analysis is made of the general and specific evolution and distribution of the precipitation in each region on São Paulo State

O presente trabalho aborda a análise de estudos anteriores a esse sobre a pluviosidade do estado de São Paulo, principalmente a tese de Doutorado do professor Sant'Anna Neto, que aborda o padrão da Pluviosidade do Estado de São Paulo. O trabalho faz uma atualização dos dados pluviométricos usados pelo professor para o período de 1994 a 2014, e a partir da construção de gráficos e cartogramas de pluviosidade, se faz uma análise geral do estado e especifica de cada região quanto a evolução e distribuição espacial anual das chuvas no estado de São Paulo
Keywords: Meteorologia - Brasil; Chuvas; Climatologia geográfica; Chuvas - Periodicidade - 1994-2014; São Paulo (Estado)